Crystal structure of chlorido-(6,6′-((1,2-phenylenebis(azanylylidene))bis(methanylylidene))bis(3-methoxyphenolato)-κ4O,N,N′,O′)iron(III), C22H18ClN2FeO4 - Cuihong Zhang; Yuan Ge; Xiaoping Huo; Liguo Yang; Xin Li; Zongcheng Miao (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C22H18ClN2FeO4, monoclinic, P21/n (no. 14), a = 7.0779(6) Å, b = 19.0203(16) Å, c = 14.7233(12) Å, β = 103.1570(10)°, V = 1930.1(3) Å3, Z = 4, Rgt(F) = 0.0278, wRref(F2) = 0.1037, T = 296(2) K.